Development of coarse corn flour technology for baking functional bread - Imanbayev, Alimzhan; Nurseitova, Zeinep; Abdurahimov, Khojiakbar; Djakhangirova, Gulnoza; Malikov, Azim (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is coarse corn flour for baking bread in the Republic of Kazakhstan. The problem to be solved is following. When using bakery products made from premium wheat flour and other varieties that contain gluten, it is possible to say that there is no health and functional direction, only the value of its nutritional value and maintaining its satiety. A promising area is the development of special types of bakery and cereal products made from coarse corn flour containing nutritious and biologically active substances: dietary fibers, fats, carbohydrates, vitamins, enzymes, micro- and macronutrients and functional proteins. As a result of the study, "Kazakhstanska" corn varieties with coarse grinding were studied and a comparative analysis with a control sample of wheat flour of water absorption capacity, in which coarse corn and the control sample showed the same result of 55.6%, with a combined change slightly. It was found that in corn flour, of all the protein fractions, the water-soluble one accounts for only 11.63% of the total amount of protein. The protein part is made up of prolamins (20.17%) and glutelins (29.20%), which are soluble in alcohol and in an alkaline solution. Corn flour contains more insoluble protein than wheat flour – 2,367 and 1,044, respectively. Corn bread made from coarse flour without admixture of wheat flour, prepared by the baking method, meets the requirements of consumers in taste and aroma, and due to this, the formulation technology has been developed. Considering this, the developed recipe technology is tailored specifically to the "Kazakhstanska" variety, which will allow the production of bread products from coarse corn flour for functional and dietary nutrition